Respuesta :
Answer:
C. 23
Step-by-step explanation:
x = 12
y = 5
x - 9 + 4y
(12) - 9 + 4(5)
12 - 9 + 20 = 23
Answer: C. 23
Step-by-step explanation:
We are given the expression [tex]x-9+4y[/tex] and we are given the values of x, and y. All we need to do it substitute the values of x and y into the expression and evaluate it.
Solving:
Given: [tex]x=12, y=5[/tex]
Evaluating:
[tex]\[\begin{aligned}x - 9 + 4y = 12 - 9 + 4(5) \\= 12 - 9 + 20 \\= 3 + 20 \\= 23\end{aligned}\][/tex]
When we plugged in the values for x and y, we got 23 as the result of the expression meaning that C is correct.
That's it!